Weakness of will and practical reason - Halley, Karina M. (Trinity College (Dublin, Ireland). Philosophy Department, 2004)
This thesis argues that a correct understanding of weakness of will (that is, freely failing to act as one thinks one has most reason to act) is crucial to a correct understanding of practical reason. Central to a theory of practical reason is the question of how practical reasons are related to motivation and action. On a common view (the Intemalism Requirement), if an agent thinks she has reason to act, then ceteris paribus, she will act. However, I argue that this view is difficult to reconcile with the possibility of weakness of will. Indeed, a proper examination of weakness o f will can serve to determine to what extent the Intemalism Requirement is acceptable and to what extent it needs to be revised or even abandoned.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin